Hip-preserving reconstruction using a customized cemented femoral endoprosthesis with a curved stem in patients with short proximal femur segments: Mid-term follow-up outcomes - You, Qi; Lu, Minxun; Min, Li; Zhang, Yuqi; Luo, Yi; Zhou, Yong; Tu, Chongqi (Frontiers in Surgery, 2022)
Background: Short metaphyseal segments that remain following extensive distal femoral tumor resection can be challenging to manage, as the residual short segments may not be sufficient to accept an intramedullary cemented stem of standard length. The present study was developed to detail preliminary findings and experiences associated with an intra-neck curved stem (INCS) reconstructive approach, with a particular focus on mechanical stability. Method: From March 2013 to August 2016, 11 total patients underwent reconstructive procedures using a customized cemented femoral endoprosthesis (CCFE) with an INCS. Measurements of femoral neck-shaft angle values were made before and after this procedure. Radiological outcomes associated with this treatment strategy over an average 63-month follow-up period were additionally assessed. Functionality was assessed based upon Musculoskeletal Tumor Society (MSTS) scores, while a visual analog scale (VAS) was used to rate pre- and postoperative pain, and any complications were noted. Results: Relative to the preoperative design, no significant differences in femoral neck–shaft angle were observed after this reconstructive procedure (p =0.410). Postoperatively, the tip of the stem was primarily positioned within the middle third of the femoral head in both lateral and posterior-anterior radiographic, supporting the accuracy of INCS positioning. The average MSTS score for these patients was 25 (range: 21-28), and VAS scores were significantly reduced after surgery (p < 0.0001). One patient exhibited local disease recurrence and ultimately succumbed to lung metastases, while two patients exhibited aseptic loosening. None of the treated patients exhibited complications such as infections, periprosthetic fractures, or prosthetic fractures as of most recent follow-up. Conclusion: CCFE with an INCS represents a viable approach to massive femoral diaphyseal defect with short proximal femur repair, as patients can achieve good functional outcomes and early weight-bearing with proper individualized rehabilitative interventions, all while exhibiting low rates of procedure-related complications.